Profiling German-speaking socially responsible investors. (29th July 2014) - Dorfleitner, Gregor; Utz, Sebastian
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to analyze the main motives of investors in allocating their money in a socially responsible (SR) way. Design/methodology/approach – The paper is based on primary data collected in a survey using an online questionnaire. This paper applies tests for continuous and categorical data and (ordered) logit models. Findings – In a multivariate analysis that investigates determinants of SR investing, this study finds little influence of the demographic factors of gender and investment volume and none of educational level. Furthermore, it shows that the regions investors allocate their money to are significant along with the preference toward the order of return, risk and liquidity. Moreover, there appears to be a gap between supply and demand of SR investments. Additionally, there are indications that a very important inducement for SR investing is the expectation of a high financial performance. Originality/value – There are very few international studies concerning the link between SR investments and the explanation of preferences with factors other than demographic ones. This study broadens the scope of the literature by providing novel empirical evidence for the German-speaking market.